2019
DOI: 10.7567/1882-0786/aaf4b2
|View full text |Cite
|
Sign up to set email alerts
|

Spin pumping as a generic probe for linear spin fluctuations: demonstration with ferromagnetic and antiferromagnetic orders, metallic and insulating electrical states

Abstract: We investigated spin injection by spin pumping from a spin-injector(NiFe) into a spin-sink to detect spin fluctuations in the spin-sink. By scanning the ordering-temperature of several magnetic transitions, we found that enhanced spin pumping due to spin fluctuations applies with several ordering states: ferromagnetic(Tb) and antiferromagnetic(NiO, NiFeOx, BiFeO3, exchange-biased and unbiased IrMn). Results also represent systematic experimental investigation supporting that the effect is independent of the me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Despite the expected long spin diffusion length of NbN (14 nm) 35 , we observe dramatically reduced spin pumping in this sample. Assuming the formation of an interfacial oxide NiFeO x layer when SIO is in direct contact with NiFe, our results suggest that either this oxide layer allows for more efficient spin current injection as already reported for HMs in contact with NiFe 36 or serves as a source of spin memory loss 37 . However, more systematic studies are required to unambiguously separate these two contributions and better understand the role of the interfacial NiFeO x layer for spin current transport.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Despite the expected long spin diffusion length of NbN (14 nm) 35 , we observe dramatically reduced spin pumping in this sample. Assuming the formation of an interfacial oxide NiFeO x layer when SIO is in direct contact with NiFe, our results suggest that either this oxide layer allows for more efficient spin current injection as already reported for HMs in contact with NiFe 36 or serves as a source of spin memory loss 37 . However, more systematic studies are required to unambiguously separate these two contributions and better understand the role of the interfacial NiFeO x layer for spin current transport.…”
supporting
confidence: 78%
“…In contrast, we only observe a weak temperature dependence for the SIO/NbN/NiFe trilayer sample, which is in accordance with earlier reports of elemental 3d-transition FMs. 39,40 We attribute the observed maximum in Gilbert damping for the SIO/NiFe bilayer and NiFe single layer samples to the antiferromagnetic ordering 16,36 of an oxide layer (thickness ∼0.5 nm) formed between SIO or STO and NiFe. This interfacial antiferromagnetic oxide layer also contributes to the damping due to magnetic fluctuations near the Néel temperature, which enhances the spin mixing conductance across the interface and thus increases the observed α.…”
mentioning
confidence: 89%
“…Interestingly, HE is slightly larger at 20 than 4 K. Such an effect has also been observed in [48] and the references therein. The exchange field of our multilayer gets very small for temperatures larger than about 60 K. This may show that the Néel temperature of antiferromagnetic NiO is placed below about 100 K due to the very small thickness of NiO layers, tNiO = 1.4 nm, according to the finite-size effect, for example, see [39,51,52]. Last but not least, the coercivity at low temperatures has a significant value close to 1.4 kOe, while in the out-of-plane direction it exceeds 1.5 kOe (Figure 7b).…”
Section: Magnetic Characterizationmentioning
confidence: 86%
“…Recently, using materials with magnetic phase transitions as spin sinks, it has been demonstrated that the spin pumping efficiency undergoes a dramatic change across the transition point. This change was attributed to the change in magnetic ordering that modulates the spin mixing conductance at the ferromagnet/spin sink interface [10][11][12][13][14] . To date, most experiments related to spincharge conversions are performed in materials with fixed structural and electrical properties.…”
mentioning
confidence: 99%